The Organoleptic Quality (Crispiness and Taste) of Rambak Cracker From Rabbit Skin on The Different Technique of Fur Picking - Dedes Amertaningtyas; Masdiana Ch. Padaga; Manik Eirry Sawitri; Khothibul Umam Al Awwaly (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2010)
This objective of this research was compare the different technique of fur picking (liming and boiling) in the organoleptic quality rambak cracker from rabbit skin on crispiness and taste. The benefit of this study is becoming useful information in the quality of rambak cracker from rabbit skin and another animal skin on the organoleptic quality (crispiness and taste). Material of this research were 20 drying rabbit skin 5 â€“ 6 months old. This research applied the experiment research with t test analize to compare the different technique of fur picking. The independent variables of this research are crispiness and taste on rambak cracker from rabbit skin. The research result showed that the different technique of fur picking had highly significant effect (P<0,01) on crispiness. The best result was liming technique of fur picking. They were characterised by sensory evaluation (crispiness) was 4 score, showed that the panelist prefered rambak cracker with liming for fur picking. Therefore, the taste in the sensory evaluation was non significant which in liming and boiling technique. In conclusion, we must use liming (4%) to produce high quality of rambak cracker from rabbit skin or another animal skin (cow, buffalo, chicken or fish). Â  Keywords : rambak cracker, rabbit skin,organoleptic quality